Estimating the structural budget balance of the Australian Government: An update - Nu Nu Win; Simon Duggan; Phil Garton; Spiro Premetis; Bonnie Li (The Australian Government, The Treasury, 2013)
This Working Paper presents an overview of structural budget balance models and the adjustments most relevant for Australia. Three models (the OECD model, the IMF model and Treasury's previously published model in the Australian Government's 2009-10 Budget and McDonald et al (2010)) are discussed. Updated estimates of the Australian Government's structural budget balance are presented alongside analysis showing the sensitivity of the results to plausible changes in key parameters. The updated structural budget balance estimates are based on the model used by McDonald et al (2010) and updated for the Australian Government's 2013-14 Budget.
Keywords: E62; H62; H69; 330; fiscal policy; cyclical adjustment; structural fiscal balance; commodity prices